ANALISIS PERAN UNIT OPERASIONAL PERUM AIRN NAVIGATION DALAM PELAYANAN LALU LINTAS UDARA UNTUK KESELAMATAN PENERBANGAN DI BANDAR UDARA ADI SOEMARMO SOLO - Yhollyza Azhari; Rosiana Ulfa (Universitas Sains dan Teknologi Komputer, 2023)
In order to create aviation work safety, the role of competent human resources is needed. Airnav Operations is one of the aviation security and safety personnel who is required to have a license who is given duties and responsibilities in aviation safety. The increase in the number of airlines today has led to the opening of routes or flight routes to various regions and abroad. So that a good air traffic service is needed to create security and safety for aviation transportation. Aviation air traffic services aim to expedite and maintain the flow of air traffic, preventing accidents on flights. This research is a qualitative type research. By conducting observations, interviews, and documentation with Airnav officers at the Solo branch of the Airnav Public Housing Office. This study aims to determine the role of Airnav officers and the obstacles they face in carrying out their duties. It is hoped that all officers will carry out their duties according to the SOP. Based on the results of the research, it shows that the role of Airnav operational officers is in accordance with the applicable SOPs, but there are still obstacles to be faced.